USE IT OR LOSE IT: MORE RECENT SEX AND ITS IMPACT ON OLDER ADULT WELL-BEING. (11th November 2018) - Lenox, M; Solow, A; Tran, V; Cabrera, C; Stripling, A
Abstract: Sexual activity as we age has been demonstrated to be an essential component of a fulfilling life. Despite the rapidly growing aging population, there remains a lack of research exploring the potentially negative impact of the absence of recent sexual activities on aspects of older adults' subjective sense of well-being. Thus, the current study aims to explore the relationship between more recent sexual episodes in older adults and facets of subjective well-being such as physical and mental health, pain intensity, and ability to engage in activities. Researchers utilized 67, 477 ageing and older adult participants from the de-identified WHO Study on Global AGEing and Adult Health (SAGE) database to explore the differences in sexual activity and several aspects of well-being through a multivariate analysis of variance (MANOVA). Results derived from a two-way MANOVA demonstrated a significant overall effect for the additive model at α=.05, Wilk's λ=.987, F(76, 106624.644)=4.804, p < .001. Significant differences were found in participants that last had sex 1–2 months ago and those that last had sex more than a year ago on subjective overall health, anxiety/worry, depression, cognition, and functional ability (vision, hearing, movement, exercise). Implications of the current findings include highlighting the importance of evaluation of the time frame of sexual activity in older adults. Future studies should explore the possible impact of implicit and explicit older adults' sexual attitudes and the inclusion of assessing recent sexual activity in screening for older adult well-being.